Kinship, Labor and Household : Understanding Women’s Work dans Feminism and Anthropology - Moore, Henrietta L. (Feminism and Anthropology, 2013)
Feminism and anthropology: The story of a relationship – Gender and status: Explaining the position of women – Kinship, labour and household: Understanding women's work – Kinship, labour and household: The changing nature of women's lives – Women and the state – Feminist anthropology: What difference does it make?
Keywords: 2000 à aujourd'hui; anthropologie; approches et analyses; cours; discipline; europe; occident; patriarcat; périodes historiques; régions géographiques; sciences humaines; soc3113; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique